Erosive Effect of Acidic Beverages and Dietary Preservatives on Extracted Human Teeth—An In Vitro Analysis - Maladkar, Shivani Ramesh; Yadav, Priyanka; Muniraja, Archana Nayaka Akllemallenahalli; Uchil, Gayathri S.; George, Linet V.; Augustine, Dominic; Rao, Roopa S.; Patil, Shankargouda; Sowmya, Samudrala Venkatesiah; Haragannavar, Vanishri C. (European Journal of Dentistry, 2022)
Objectives Frequent consumption of acidic beverages and dietary preservatives in younger generation, diet-conscious (celebrities), and obese individuals have a rapid impact on demineralization of the teeth. An attempt was made to analyze the erosive potential of various acidic beverages.Materials and Methods One hundred and ninety extracted human permanent teeth were sectioned longitudinally, pre-weighed, randomly grouped, and placed in nine acidic beverages (200 mL) with predetermined pH, i.e., three commercially available fruit juices, three carbonated drinks, and three dietary preservatives.Statistical Analysis The sectioned specimens (n = 10) were analyzed at time intervals of 12, 24, 48, and 96 days. Mean weight loss was calculated, and surface changes were assessed under a stereomicroscope. The demineralization pattern and microscopic changes were observed under a compound and polarizing microscope. One-way analysis of variance test followed by Tukey's post-hoc analysis was employed.Results Overall the maximum demineralizing effect was caused by vinegar and apple cider. In the fruit juices category, lemon juice induced significant changes, while in the carbonated drinks category Coca-Cola induced the maximum changes and in the category of food preservatives vinegar induced the maximum changes. Severe discoloration was seen with respect to Coca-Cola followed by Mountain Dew (carbonated drink).Conclusion The present study is unique as three different types of microscopes have been employed and both dentin and enamel of permanent teeth have been analyzed. In addition, the effect of dietary preservatives on hard tissues was evaluated. Oral health educators can reinforce important practices such as decreasing the frequency of consumption and time duration of beverage contact with the teeth. Also, the use of mouth rinses and buffering agents after the consumption of dietary beverages can be advocated along with regular fluoride application for those who are regular consumers.
Keywords: erosion; acidic beverages; demineralization; dental hard tissues; dietary preservatives; polarizing microscope; stereomicroscope